Treatment preferences of patients with relapsed or refractory multiple myeloma in the United States, United Kingdom, Italy, Germany, France, and Spain: results from a discrete choice experiment - Thomas, Caitlin; Ailawadhi, Sikander; Popat, Rakesh; Kleinman, David; Ross, Melissa M.; Gorsh, Boris; Mulnick, Sarah; O’Neill, Alicia; Paka, Prani; Hanna, Maya; Krucien, Nicolas; Molinari, Alexa; et al. (Frontiers in Medicine, 2023)
Introduction: Newer treatment options for relapsed/refractory multiple myeloma (RRMM) with efficacy and safety profiles that differ from traditional therapies have facilitated personalized management strategies to optimize patient outcomes. In the context of such personalized management, understanding how treatment characteristics influence patients' preferences is essential. This study assessed patients' preferences for RRMM treatment attributes and determined trade-offs between potential benefits, administration procedures, and adverse effects.Methods: Patients' preferences were evaluated using a discrete choice experiment (DCE). Patients with RRMM who reported failing at least two lines of anti-myeloma treatment (immunomodulatory agent and a proteasome inhibitor [PI]) or ≥3 lines (including ≥1 PI, immunomodulatory agent, or anti-CD38 monoclonal antibody), were recruited across the US, UK, Italy, Germany, France, and Spain. DCE attributes and levels were identified using a targeted literature review, a review of clinical data for relevant RRMM treatments, qualitative patient interviews, and input from clinical and myeloma patient experts. The DCE was administered within an online survey from February−June 2022. Preference data were analyzed using an error-component logit model and willingness to make trade-offs for potential benefits, and relative attribute importance scores were calculated.Results: Overall, 296 patients from the US (n=100), UK (n=49), Italy (n=45), Germany (n=43), France (n=39), and Spain (n=20) participated in the DCE. Mean (standard deviation) age was 63.8 (8.0) years, 84% had a caregiver, and patients had a median of 3 (range: 2-8) prior lines of therapy. Efficacy attributes most influenced patients' preferences, with increasing overall response rate (25% to 85%) and overall survival (6 months to 2 years) contributing to 50% of treatment decision-making. Administration procedures were also considered important to patients. Avoiding individual side effects was considered relatively less important, with patients willing to tolerate increases in side effects for gains in efficacy. Patient characteristics such as rate of disease progression, sociodemographics, or clinical characteristics also influenced treatment preferences.Patients with RRMM were willing to tolerate increased risk of side effects for higher efficacy. Preferences and risk tolerance varied between patients, with preference patterns differing by certain patient characteristics. This highlights the importance of shared decision-making for optimal treatment selection and patient outcomes.